Destination: demain - Barrieau, Pierre; Richard, Geneviève (Continuité, 2024)
issued: 2024-21-00
Keywords: Transport en commun

L'histoire du chemin du Roy, XVIII-XXᵉ siècles : étude historique d'une route, d'un symbole, d'un récit - Fortin-Dupuis, Simon (Université Laval, 2024)
Keywords: Routes

Tramway à Montréal-1861 à 1959 - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
issued: 2024-22-00
Keywords: Montreal Street Railway Company; Tramways

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-23-00
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)

MUIR, HENRIETTA LOUISE - Roome, Patricia (Dictionnaire biographique du Canada, 2023)

Une mesure d'origine britannique. Les barrières à péage à Outremont - Waché, Gabriel; Bizier, Hélène-Andrée (Mémoire vivante, 2023)
issued: 2023-21-00
Keywords: Outremont; Routes

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

DUPUIS, JOSEPH-NARCISSE (Dictionnaire biographique du Canada, 2022)

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-21-00
Keywords: Chemins de fer; Paysages

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-24-00
Keywords: Routes; Saint-Laurent (rue)

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

À la croisée des chemins : mise en place et implantation du réseau de télégraphe électrique canadien, 1846-1867 - Dumais-Gingras, Pierre (Université du Québec à Montréal, 2021)
Keywords: Téléphone

Au croisement de la perte de mémoire et de la créativité communautaire: de nouvelles innovations dans les anciens ateliers ferroviaires de Pointe-Saint-Charles - Elliott, Andrew (Bulletin de l'AQPI, 2021)
issued: 2021-21-00
Keywords: Canadien National; Chemins de fer; Conservation; Grand Tronc; Patrimoine

“The Severity of This Service…” Canadien Inland Mariners in the Early Post-Conquest Era, 1760 to 1817 - More, John David (Université Queen's, 2021)
Keywords: Guerre; Navigation

1800 to 1830. Montréal, Building British Metropolis - Robert, Jean-Claude (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne’s Market and the Parliament of the Province of Canada, 2021)
Translators: _:n117 Translators: _:n62493
Keywords: Métropole; Port

De 1800 à 1830. Montréal, jeune métropole britannique - Robert, Jean-Claude (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Métropole; Port

Le canal de Lachine: un paysage en constant mouvement - Paradis, Matthieu; Gelly, Alain (Histoire Québec, 2020)
Number: 4
Keywords: Lachine (canal); Paysages

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-22-00
Keywords: Chemins de fer; Musique; Noirs; Travail

Ponts et traverses de la rivière des Prairies - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-24-00
Keywords: Ponts; Rivière des Prairies; Rivière-des-Prairies